An Exact A-Based Tree Search Algorithm for TSP With Sequence-and-Load Dependent Risk - Cha, Hyungjoo; Lee, Chanho; Xie, Chi; Lu, Qing-Chang; Eun, Joonyup; Cheong, Taesu (IEEE transactions on intelligent transportation systems, 2024)
The hazardous material transportation requires extensive care owing to the disastrous consequences of accidents, such as chemical spills or radioactive exposures. Consequently, a minimum risk delivery plan that is dynamically decided by the cargo load of the vehicle at each customer must be scheduled. We introduce a traveling salesman problem (TSP) with a sequence-and-load dependent risk, which differs from the conventional TSP as the arc costs are determined by the hazardous cargo load at each decision epoch. We define our problem in a dynamic programming formulation and present mixed-integer linear program with a nonlinear objective function. To efficiently retrieve exact optimal solutions, we propose an iterative-deepening A*-based tree search algorithm using admissible lower and efficient upper bound algorithms for guaranteed optimality. Numerical experiments indicate that the proposed algorithm outperforms a current state-of-the-art solver. An ablation study and sensitivity analysis demonstrate the effectiveness of the proposed algorithm and derive managerial insights.